Increasing Mathematical Problem-Solving Ability Through Models Problem-Based Learning on Cube and Block Material - Wulandari, Irma (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2024)
This research aims to improve students' mathematical problem-solving abilities through models of problem-based learning. This research is classroom action research (PTK) conducted on 29 students in class VII.4 of SMP N 61 Palembang. Classroom action research is planned in two cycles. Each cycle goes through four stages of activity, namely planning, action, observation and reflection. Indicators of this research include understanding the problem, planning, solving the problem and interpreting the results obtained. The results obtained from this research in cycle I was through the model problem-based learning achieved an average score for the mathematical problem-solving ability of 70 in cycle I, while in cycle II it was 79.66. Based on these results it can be concluded that the model problem-based learning can improve students' mathematical problem-solving abilities in cube and block material.